Guidelines of the Polish Ophthalmological Society on how to deal with ophthalmic patients during the COVID-19 epidemic - Szaflik, Jacek P.; Stopa, Marcin; Horban, Andrzej; Przybek-Skrzypecka, Joanna; Bakunowicz-Łazarczyk, Alina; Dobrowolski, Dariusz; Grabska-Liberek, Iwona; Izdebska, Justyna; Kałużny, Jakub; Mackiewicz, Jerzy; Misiuk-Hojło, Marta; Mrukwa-Kominek, Ewa; et al. (Klinika Oczna / Acta Ophthalmologica Polonica, 2020)
SARS-CoV-2 is a coronavirus that causes COVID-19 (coronavirus disease 2019). In March 2020 the World Health Organization (WHO) declared a coronavirus pandemic. Individuals employed at ophthalmic departments and clinics are especially exposed to transmission of the virus due to the specific nature of an ophthalmic examination. The Polish Ophthalmological Society presents Guidelines that recommend implementation of an appropriate level of safety measures in ophthalmic care provided to patients.